1992
DOI: 10.4269/ajtmh.1992.47.271
|View full text |Cite
|
Sign up to set email alerts
|

Ovalocytosis Protects against Severe Malaria Parasitemia in the Malayan Aborigines

Abstract: The malaria parasite rates and densities were compared in 79 ovalocytic-normocytic pairs of Malayan Aborigines matched for age, sex, proximity of residence to each other, and use of bed nets when sleeping in their jungle settlement in central Peninsular Malaysia. Malaria infection was determined from thick and thin Giemsa-stained blood films collected monthly for a period of six months. Blood films from ovalocytic individuals were found to be positive for malaria less often than in persons with normal red bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Protection against malarial infection by ovalocytoses of unspecified genotypes has also been demonstrated in populations in nearby Southeast Asia (8,68). Ovalocytic RBCs resist invasion by P. falciparum (110) and by Plasmodium knowlesi (85), a simian malaria parasite with similar RBC invasion characteristics to P. vivax.…”
Section: Ovalocytosismentioning
confidence: 99%
“…Protection against malarial infection by ovalocytoses of unspecified genotypes has also been demonstrated in populations in nearby Southeast Asia (8,68). Ovalocytic RBCs resist invasion by P. falciparum (110) and by Plasmodium knowlesi (85), a simian malaria parasite with similar RBC invasion characteristics to P. vivax.…”
Section: Ovalocytosismentioning
confidence: 99%
“…On the other hand, SAO individuals are fully susceptible to severe malaria anemia and clinical uncomplicated malaria. 18 Although early studies, conducted before the presence of the SAO trait could be determined unambiguously by polymerase chain reaction (PCR), suggested that SAO individuals exhibit some degree of protection against prevalence of malaria parasites or against high-density P falciparum infections, [20][21][22] later studies demonstrated that SAO individuals suffer high-density infections by P falciparum and this trait only has minor effects, if any, on the prevalence and density of P falciparum infections. 18,23 Our recent finding that SAO infected RBCs (IRBCs) have altered adherence properties compared with normal IRBCs (A.C., M. Mellombo, C.S.…”
Section: Introductionmentioning
confidence: 99%
“…The higher frequencies of SAO found in adults than in the young of the same population in malaria endemic areas (Baer et al, 1976) also supported this hypothesis and suggested a selective advantage of SAO in such areas. However, several studies on malaria resistance of SAO are controversial in terms of parasite density or Plasmodium species (Baer et al, 1976;Serjeantson et al, 1977;Cattani et al, 1987;Foo et al, 1992).…”
Section: Introductionmentioning
confidence: 99%